Major and trace elemental compositions of the upper Carboniferous Batamayineishan mudrocks, Wulungu area, Junggar Basin, China: Implications for controls on the formation of the organic-rich source rocks. (March 2018) - Zhang, Kuihua; Jin, Wujun; Lin, Huixi; Dong, Caiyuan; Wu, Shangrong
Abstract: The upper Carboniferous Batamayineishan mudstones are an important and effective gas source rock in the Wulungu area. These sediments are rich in organic matter, however, organic matter accumulation has not been studied before in these mudstones. The major and trace elements were used to reconstruct the depositional environments of these sediments and to improve our understanding of the factors controlling organic matter accumulation. Major and trace elements data indicate that: (1) paleoweathering was low to intermediate in the source terrain; (2) paleoclimate was hot and arid during late Carboniferous in the Wulungu area; (3) low paleoproductivity may have been induced by the low input of nutrients caused by the hot arid climate; (4) the Batamayineishan mudstones were deposited under a reducing environment; (5) organic matter accumulation in these studied deposits was mainly controlled by the input of higher plants rather than redox conditions and paleoproductivity. Highlights: Paleoweathering was low to intermediate in the source terrain. Paleoclimate was hot and arid during late Carboniferous. The mudstones were deposited under a reducing environment. Organic matter accumulation was controlled by the input of higher plants.